EXPRESSION OF CERTAIN MORPHOLOGICAL TRAIT INDICATORS IN THE T-826 LINE OF GOSSYPIUM HIRSUTUM L. (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article presents a comparative analysis of the morpho-economic traits of the T-826 line belonging to Gossypium hirsutum L. with the standard varieties Namangan-77 and S-6524. The study was conducted in 2023 under the conditions of the Tashkent region based on phenological observations of 100 plants.According to the analysis results, the main stem height of the T-826 line was 114.8 cm, which was lower than that of Namangan-77 (117.5 cm) and S-6524 (118.1 cm). However, in terms of the number of fruiting branches, T-826 (12.3 branches) showed higher values compared to both standard varieties (11.7 and 11.0 branches, respectively).The T-826 line also demonstrated superiority in the number of locules per boll (4.70) compared with Namangan-77 (4.40) and S-6524 (4.61). In general, although the T-826 line exhibited a relatively shorter plant height, positive differences were observed in generative traits (yield components).The obtained results indicate that the T-826 line can be considered a promising source with high yield potential for use in cotton breeding programs.